2015
DOI: 10.1111/bjd.13575
|View full text |Cite
|
Sign up to set email alerts
|

Limited exposure to ambient ultraviolet radiation and 25-hydroxyvitamin D levels: a systematic review

Abstract: What's already known about this topic? Hypovitaminosis D is common worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 90 publications
2
17
0
Order By: Relevance
“…Seasonal changes of D3 concentrations, for example, due to sun exposure have been verified [3,25,26]. However, this fact still often remains unconsidered, in particular, the aspect of physiological vitamin D3 storage [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal changes of D3 concentrations, for example, due to sun exposure have been verified [3,25,26]. However, this fact still often remains unconsidered, in particular, the aspect of physiological vitamin D3 storage [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that D3 synthesis depends on the UVR exposure [26]. Early studies from Webb et al [25] verified that the ambient UVR in higher latitudes nonpolar regions during winter is insufficient to generate D3, showing that pre-vitamin D is not synthesized, for example, from November to February in Boston, USA (42°N) or between October and March in Edmonton, Canada (52°N).…”
Section: Three-month Quartile Changes Of Vitamin D3 Serum Concentratimentioning
confidence: 99%
“… 1 Variations in the mammalian reproductive cycle are among the best documented biological phenomena studied in relation to seasonality, with the level of fertility changing at certain times of the year to improve the chances of survival of offspring. 2 However, there is evidence that many other physiological functions and human disease-related conditions exhibit similar seasonal and also circadian patterns, for example, cardiovascular, 3 physiological state, 4 autoimmune, 5 cutaneous, 6 , 7 and psychiatric disorders. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Obviously this is not the case, and in a recent systematic review [33], it was demonstrated that many healthy adults in different populations can maintain adequate S-25OHD levels despite negligible UV exposure for several months of the year. Therefore, a key question is, how long do vitamin D stores last?…”
mentioning
confidence: 99%